PENGEMBANGAN E-LKPD MENGGUNAKAN PENDEKATAN PEMBELAJARAN MENDALAM TERINTEGRASI KEARIFAN LOKAL MATERI KEANEKARAGAMAN HAYATI UNTUK MENUMBUHKAN KEPEDULIAN LINGKUNGAN PESERTA DIDIK - Oktavian, Muhammad Taufik Pratama; Ambarwati, Reni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low environmental awareness among students is a serious challenge, reflected in littering, damaging school facilities, and a lack of conservation awareness, which highlights the need for contextual and meaningful teaching material. This study aimed to produce an electronic student worksheet (E-LKPD) using a deep learning approach integrated with local wisdom that is valid, practical, and effective for fostering students' environmental care. This research and development study used the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). A limited trial involved 21 tenth-grade students at SMAS Kartika IV-3 Surabaya. Validity was assessed by two expert validators, a learning expert and a content expert. Practicality was measured through an implementation observation sheet and teacher and student response questionnaires. Effectiveness was measured using an environmental care attitude questionnaire covering three indicators: environmental awareness, concern for biodiversity, and responsibility for environmental conservation. The results showed that the E-LKPD obtained a validity score of 100%, categorized as very valid. Practicality reached 97% for learning implementation, 100% for teacher response, and 91% for student response, all categorized as very practical. Effectiveness, based on the achievement of environmental care indicators, reached 85% for environmental awareness, 84% for biodiversity concern, and 73% for conservation responsibility, with an overall average of 81% in the caring category. These findings indicate that the developed E-LKPD is valid, practical, and effective for fostering students' environmental care attitudes.